Draft Fourth Five Year Plan (1966-71) Madhya Pradesh - Planning Commission (Planning Commission, 1966)
Madhya Pradesh is the biggest State of India. It covers an area of 171,217 square miles which is 13.89 per cent of the total area of the country. About 32 per cent of its area is covered by forests. The State lies across the table land of Central India and according to physical features; it can be divided into the Gird region, the Malwa plateau, the Narbada valley, the Satpura range and the Chhatisgarh plains. The State has a network of rivers which flow in all directions. The main rivers are the Chambal, the Setwa, the Sone, the Narbada, the Tapti, the Mahanadi and the Indravati. The annual rainfall in the State varies from 65 in Mahaknshal region, 30 ” to 405 in Malwa region, 30"" to 35"" in Vindhya Pradesh region and 30"" to 50"" in Bhopal region. For administrative purposes, the State is divided into 7 divisions, 43 districts, 190 tahsils, 452 community development blocks. It has 70,414 inhabited villages and 219 towns
Government of Madhya Pradesh
Government of Madhya Pradesh Planning and Development Department
Keywords: General features of the State; Development in the economy in Madhya Pradesh; Size and contents of the fourth five year plan an outline; Employment and Manpower; Programmes under different sectors of the fourth plan; Veterinary and Animal husbandry including dairying and milk supply and fisheries; Forests and soil conservation; Community development including Panchayats; Mineral Development